An evaluation of a test-negative design for EV-71 vaccine from a randomized controlled trial - Li Zhang; Mingwei Wei; Pengfei Jin; Jingxin Li; Fengcai Zhu (Taylor & Francis Group, 2021)
Background: The test-negative design has been used widely in evaluation of various vaccines' effectiveness, such as influenza, rotavirus, and so on. Recently, there have been some studies about EV-71 vaccine effectiveness by using test-negative design(TND). However, the validity of the TND application in EV-71 vaccines has not been evaluated. Methods: This study is set upon prior methods to evaluate the validity of TND for influenza vaccine by using a randomized controlled clinical trial database. Vaccine effectiveness estimated by TND (VE-TND) in modified intention-to-treat population (mITT) and per-protocol-set population(PPS) was derived from a large randomized placebo-controlled clinical trial (RCT) of inactivated monovalent EV-71 vaccine in China. Derived VE-TND estimates were compared to the original vaccine efficacy results in RCT (VE-RCT). Results: We totally enrolled 7325 participants who seeked medical care for suspected EV-71 infected diseases during the surveillance. There are no significant differences between cases(test-positive) and controls(test-negative) on sex, age, height, and weight. TND vaccine effectiveness estimates were similar to original RCT vaccine efficacy estimates, both in modified intention-to-treat population and per-protocol populations. Conclusions: This study supports that TND, as an appropriate observational study design is valid to measure EV-71 vaccine effectiveness.